AL type cardiac amyloidosis: a devastating fatal disease - Adeel Nasrullah; Anam Javed; Thejus T Jayakrishnan; Aaron Brumbaugh; Ariel Sandhu; Brent Hardman (Journal of Community Hospital Internal Medicine Perspectives, 2021)
Introduction Cardiac amyloidosis is a rare entity with a grave prognosis. Due to the low index of suspicion secondary to non-specific symptoms, it is often diagnosed at an advanced stage with multi-organ involvement. Methods We report a case of systemic AL amyloidosis with predominant cardiac and renal involvement associated with multiple myeloma. Case Summary A 60-year-old male presented with progressive anasarca, orthopnea and weight gain over 8 months. On clinical examination, 3+ pitting edema was found in bilateral extremities and scrotum. Serum N-type proBNP and troponin T were elevated, and EKG showed diffuse low voltage QRS, right axis deviation, and 1st degree AV block. Echocardiography revealed granular myocardium, biventricular hypertrophy, bi-atrial dilation and apical sparing pattern on global longitudinal strain which was suggestive of cardiac amyloidosis. Light chain assessment showed elevated kappa and lambda chains with kappa to lambda ratio of 16.2. Endomyocardial biopsy revealed AL type cardiac amyloidosis, and bone marrow biopsy confirmed the diagnosis of multiple myeloma. He received six cycles of bortezomib, cyclophosphamide, and dexamethasone but continued to deteriorate. He experienced an episode of cardiac arrest following which he had a return of spontaneous circulation but due to poor prognosis, the family opted for pursuing comfort measures only. Conclusions Cardiac involvement in AL type amyloidosis imparts significant morbidity and mortality. The management of cardiac amyloidosis entails a multidisciplinary approach with an emphasis on cardiology and oncology. Despite the novel diagnostic modalities and treatment regimens, the outcome for AL-type cardiac amyloidosis remains poor.